Synchronous excitation in the superficial and deep layers of the medial entorhinal cortex precedes early sharp waves in the neonatal rat hippocampus - Shipkov, Dmitrii; Nasretdinov, Azat; Khazipov, Roustem; Valeeva, Guzel (Frontiers in Cellular Neuroscience, 2024)
Early Sharp Waves (eSPWs) are the earliest pattern of network activity in the developing hippocampus of neonatal rodents. eSPWs were originally considered to be an immature prototype of adult SPWs, which are spontaneous top-down hippocampal events that are self-generated in the hippocampal circuitry. However, recent studies have shifted this paradigm to a bottom-up model of eSPW genesis, in which eSPWs are primarily driven by the inputs from the layers 2/3 of the medial entorhinal cortex (MEC). A hallmark of the adult SPWs is the relay of information from the CA1 hippocampus to target structures, including deep layers of the EC. Whether and how deep layers of the MEC are activated during eSPWs in the neonates remains elusive. In this study, we investigated activity in layer 5 of the MEC of neonatal rat pups during eSPWs using silicone probe recordings from the MEC and CA1 hippocampus. We found that neurons in deep and superficial layers of the MEC fire synchronously during MEC sharp potentials, and that neuronal firing in both superficial and deep layers of the MEC precedes the activation of CA1 neurons during eSPWs. Thus, the sequence of activation of CA1 hippocampal neurons and deep EC neurons during sharp waves reverses during development, from a lead of deep EC neurons during eSPWs in neonates to a lead of CA1 neurons during adult SPWs. These findings suggest another important difference in the generative mechanisms and possible functional roles of eSPWs compared to adult SPWs.